What do unions do… with digital technologies? An affordance approach. (2nd March 2021) - Hennebert, Marc‐Antonin; Pasquier, Vincent; Lévesque, Christian
Abstract: This article examines the affordances that digital technologies offer to labour unions. The results of our study of 13 trade unions in Canada contrast with the prevailing techno‐deterministic perspectives in the literature which describe digital technologies as fundamentally good, bad or neutral for unions. By adopting an affordance approach, our paper examines how union actors perceive digital technology utility and constraints across five union core functions. The study identifies four digital information and communication technology affordances for unions (visibility, intensification, aggregation and addressability) and contributes to the literature on union renewal by showing how these affordances interact in a complex way and can reinforce trade unions' capabilities.